2014
DOI: 10.1155/2014/724258
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions and Expected Effects to Therapy with Subcutaneous Mistletoe Extracts (Viscum album L.) in Cancer Patients

Abstract: Background. In Europe, mistletoe extracts are widely used as a complementary cancer therapy. We assessed the safety of subcutaneous mistletoe as a conjunctive therapy in cancer patients within an anthroposophic medicine setting in Germany. Methods. A multicentre, observational study was performed within the Network Oncology. Suspected mistletoe adverse drug reactions (ADRs) were described by frequency, causality, severity, and seriousness. Potential risk factors, dose relationships and drug-drug interactions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 52 publications
5
67
0
2
Order By: Relevance
“…Patients were also more likely to experience multiple ADRs to IT injections. 36,37 These differences were not likely to be a result of differing demographics because there were no significant differences between the 3 treatment groups in terms of age and gender. The elevated frequency of ADRs in response to IT injections compared with SC injections might be explained by the fact that IT injections typically involve administration of much higher doses of mistletoe.…”
Section: Figurementioning
confidence: 95%
See 3 more Smart Citations
“…Patients were also more likely to experience multiple ADRs to IT injections. 36,37 These differences were not likely to be a result of differing demographics because there were no significant differences between the 3 treatment groups in terms of age and gender. The elevated frequency of ADRs in response to IT injections compared with SC injections might be explained by the fact that IT injections typically involve administration of much higher doses of mistletoe.…”
Section: Figurementioning
confidence: 95%
“…36,37 It was found that patients were almost 3 times more likely to experience an ADR to IT injections compared with SC injections and 5 times more likely compared with IV infusions (Figure 2). …”
Section: Comparison Of It Mistletoe With Subcutaneous and IV Mistletoementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, scientists have investigated and determined that bioactive compounds are responsible for the pharmacological effects of medicinal plants, and various phytochemicals have been studied to determine the therapeutic effect of natural products (Chen et al ., ). Studies have shown the effectiveness of medicinal plants in treating diseases such as cancer (Steele et al ., ), Alzheimer's disease (Howes and Houghton, ), chronic obstructive pulmonary disease (Chen et al ., ), diarrhea and cholera secretions (Tradtrantip et al ., ), stomatitis (Gavanji et al ., ), and periodontal disease (Agrawal et al ., ; Gupta et al ., ).…”
Section: Introductionmentioning
confidence: 99%